Asymmetric adjustment of diesel or petrol retail prices to crude oil price movements: New Zealand evidence - Alom, Fardous; Neil, Ritson (Blackwell Publishing Ltd, 2012)
This study has twofold objectives. Firstly, to examine the short- and long-run relationships between diesel or petrol retail prices in NewZealand and crude oil prices and, secondly, to assess the response of retail sector price movements to changes in crude oil prices. The study uses both standard and hidden asymmetric cointegration methods. The major findings are as follows: the prices of diesel and petrol maintain both short- and long-run relationships with crude oil prices although the pass-through rates differ. Diesel prices are found to be symmetric in response to the changes in crude oil prices, while petrol prices respond asymmetrically to changes in crude oil prices. When crude oil prices increase, petrol prices in New Zealand increase immediately and not vice versa. The reasons for the symmetric pricing behaviour might include higher demand for petrol than diesel, individual and tourist-type customers rather than commercial and industrial customers, search costs, revenue maximizing behavior of retailers based on high demand, and government taxes and levies.